Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan Mie Gacoan pada Mahasiswa di Jakarta Barat - Fajari Wulan Suci; Henny Armaniah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Mie gacoan is a fast-growing Indonesian food and beverage company. The word 'gacoan' is derived from the Javanese word meaning a mainstay. This research aims to investigate the effect of service quality and price on the satisfaction of gacoan noodle customers on students in West Jakarta. The research method used a quantitative approach by spreading questionnaires to 96 respondents through a purposive sampling method and making observations to evaluate service quality. This analysis shows that service quality and price have a significant positive influence on customer satisfaction. individually, service quality has a significance value of 0.000 with a Thitung value of 6,670 and price has a significance value of 0.009 with a Thitung value of 2,650. Simultaneously, the Fhitung value of 46,202 with a significance of 0.000, this shows a significant influence from both variables. In conclusion, there is a positive and significant effect of service quality and price on the satisfaction of gacoan noodle customers on students in west jakarta, both individually and simultaneously. These findings provide insight for restaurant owners to improve marketing strategies and customer service. By understanding these factors, restaurants can more effectively attract and retain customers.